The botany of the Antarctic voyage of H. M. discovery ships Erebus and Terror in the Years 1839-1843, under the command of Captain Sir James Clark Ross. - Hooker, Joseph Dalton, Sir, 1817-1911; Hooker, Joseph Dalton, Sir, 1817-1911. Flora Tasmaniae; Hooker, Joseph Dalton, Sir, 1817-1911. Flora Novae-Zelandiae; Hooker, Joseph Dalton, Sir, 1817-1911. Flora Antarctica (London, Reeve Brothers, 1844)
Mode of access: Internet.